SHORT NOTICES - Langton, Daniel (Journal of Semitic studies, 2003)
Messianic Judaism Dan Cohn-Sherbok . Continuum, London and New York , 2000. Pp. xii + 234. Price: £17.99 paperback/£45.00 hardback. ISBN: 0-8264-54585.